Double-pole approximation for leading-order semi-leptonic vector-boson scattering at the LHC - Ansgar Denner; Daniele Lombardi; Christopher Schwan (Journal of High Energy Physics)
Abstract Measuring vector-boson scattering beyond the fully-leptonic final state is becoming possible at the LHC, which demands to have a solid control on the theory predictions for all final states of this class of processes. In this work we present a full off-shell leading-order calculation for the process pp → ℓ + ν ℓ + 4j in two fiducial regions which are particularly relevant for its experimental measurement. In addition to the fully electroweak order, i.e. O α 6 $$ \mathcal{O}\left(α^6\right) $$ , we complement our results with O α s α 5 $$ \mathcal{O}\left(α_{s}{α}^5\right) $$ and O α s 2 α 4 $$ \mathcal{O}\left(α_{s}^2α^4\right) $$ for inclusive predictions. At O α 6 $$ \mathcal{O}\left(α^6\right) $$ we present for the first time a systematic treatment of the process in double-pole approximation and we perform a detailed study of its range of validity by considering inclusive and differential predictions compared to the full off-shell calculation.